Deep neck infections – Survey from an ENT department - Pereira, Sonia (2011)
Given the complexity, deep location and significant morbidity of deep neck space infections, their diagnosis and treatment remain an important medico-surgical challenge. As these infections are frequently caused by tonsillar and pharyngeal infections, Otolaryngologists are often called to lead with difficult problems.Aiming to analyze deep neck space infections occurred during the last five years in Hospital de São José’s Department of Otolaryngology, we present a retrospective study of patients followed for this pathology since January 2004.High prevalence of tonsillar infections was confirmed, with low morbidity in cases where adequate treatment was provided. The most serious complication was necrotizing mediastinitis, rare but with significant mortality, most of the time in patients with underlying systemic diseases.High prevalence of oro-pharyngeal pathology as a common etiology of these infections should alert Otolaryngologists to carefully supervise their clinical evolution. Prompt diagnosis and rapid medico-surgical therapy are essential to assure a better prognosis.